Vietnam and Iraq Wars: Parallelism and Its Impact on U.S. Foreign Policy - Abdul Rohman (Jurnal Komunikasi, 2011)
This article describes certain policies were developed in Vietnam and Iraq Wars in term of the quality of intelligence and congressional decision-making within two wars. Two similarities are identified: a) the failure of intelligence in both war policies; and b) the controversy surrounding the policies to declare both wars. The Vietnam and Iraq wars have similarities in terms of the quality of intelligence and presidential decision-making to go to war. The fall and manipulation of intelligence and the increase of executive powers colored policies in both war declarations. Pluralism and elite-power theory shape U.S. foreign policy in which a few groups/elites govern the many. A critical perspective was presented to improve the quality of foreign policy by more listening to what allies consider being important and by gaining multilateral cooperation to overcome major multinational threats.